Pelatihan Metode Pembelajaran Klinik Preceptorship di RSI Banjarnegara - Sumarni, Tri; Indri; Wasis (Jurnal Pengabdian Masyarakat - PIMAS, 2024)
Preceptors are health professionals who are skilled in a discipline, but may have little ability to guide students in practice. If preceptors do not fully understand their role in the clinical learning process, then clinical learning goals will not be achieved. Therefore, it is very important that preceptors receive training on preceptorship clinical learning methods. This community service activity aims to deepen the preceptor's understanding regarding clinical education management, clinical learning methods, clinical learning assessment. The method of implementing the service is knowledge screening, training and discussion about preceptorship clinical learning methods and bedside teaching simulations. This activity was attended by 20 nurses. Most service participants were aged between 41-50 years (85%), female (60%), trained as nurses (100%), and had worked for more than five years (65%). Regarding preceptors' knowledge of clinical teaching methods, most were in the poor category (70%) before training, but most were in the good category (90%) after training. Keywords : training, preceptorship clinical learning methods